close
標題:
呢條係中三的數學
發問:
13/(6(a^2-b^2)-5ab)- 5/(6(a^2+b^2)-13ab)+ 8/9a^2-4b^2
最佳解答:
13/(6(a^2-b^2)-5ab)- 5/(6(a^2+b^2)-13ab)+ 8/(9a^2-4b^2) = 13/(6a^2 - 5ab - 6b^2) - 5/(6a^2 - 13ab + 6b^2) + 8/(3a-2b)(3a+2b) = 13/(3a+2b)(2a-3b) - 5/(3a-2b)(2a-3b) + 8/(3a-2b)(3a+2b) = 13(3a-2b) / (3a+2b)(2a-3b)(3a-2b) - 5(3a+2b) /(3a-2b)(2a-3b)(3a+2b) + 8(2a-3b) / (3a-2b)(3a+2b)(2a-3b) = (39a-26b - 15a-10b + 16a-24b) / (3a-2b)(3a+2b)(2a-3b) = (40a - 60b) / (3a-2b)(3a+2b)(2a-3b) = 20(2a-3b) / (3a-2b)(3a+2b)(2a-3b) = 20 / (3a-2b)(3a+2b) 圖片參考:http://l.yimg.com/f/i/tw/ugc/rte/smiley_32.gif
此文章來自奇摩知識+如有不便請留言告知
其他解答:
文章標籤
全站熱搜
留言列表